(untitled) (Bangladesh Journal of Medical Science, 2025)
Objective The aim of this study was to evaluate and compare the effects of two different dose of intrathecal morphine adjunct to ultra-low dose of naloxone on pain intensity after cesarean section. Methods In this double-blind randomized clinical trial, 78 women over 18 years of age who referred to the Imam Khomeini Hospital in Sari for elective cesarean section were allocated randomly to receive either intrathecal morphine with doses of 100 μg or 200 μg, adjunct to ultra-low dose of naloxone (20 ng). Patients’ pain intensity were assessed using the VAS at 2, 4, 6 and 24 hours postoperatively. Also, the occurrence of adverse effects (pruritus, nausea, vomiting and ileus) in two groups were evaluated during the study period. Results The findings of this study indicated a significant difference in pain intensity between the two groups throughout the study period (p<0.05). Ileus was not significantly different between the two groups (P=0.48). However, using morphine at a dose of 200 μg with naloxone was associated with significantly lower rate of nausea and pruritus (P<0.001). Conclusion In the present study, patients receiving morphine at a dose of 200 μg with naloxone (20 ng) experienced significantly less pain intensity than the group receiving morphine at a dose of 100 μg with naloxone. In addition, the rate of nausea and pruritus in the group receiving morphine at a dose of 200 μg with naloxone was significantly lower than the other group. BJMS, Vol. 24 No. 04 October’25 Page : 1131-1137